Pengaruh Model Heuristik Vee Berorientasi Etnografi Tehadap Berpikir Kritis Dan Literasi Sains Siswa Sekolah Dasar - Apriana, Dina; Suastra, I Wayan; Arnyana, Ida Bagus Putu (Universitas Negeri Makassar, 2023)
The objective of this study was to determine the effect of using the Ethnographically oriented Vee Heuristic learning model to improve students' critical thinking skills and scientific literacy in elementary schools. The research used a quasi-experimental method with a post-test only control group design. The sample consisted of 36 students of class V of SDN 1 Labuhan Haji determined by group random sampling. To test the research hypothesis, using one-way Manova statistical data. Based on the results of the simultaneous hypothesis analysis, it shows that there are significant differences in critical thinking skills and scientific literacy between students who follow the Vee Heuristic learning model and students who follow conventional learning models. The use of the ethnographic-oriented Vee Heuristic learning model can manage students' understanding in a structured way to solve problems associated with culture and science in their environment.